Tailoring Charge Donor–Acceptor Interaction in CsPbBr3 Perovskite Nanocrystals through Ligand Exchange - Syed Abdul Basit Shah; Sushant Ghimire; Rostyslav Lesyuk; Maria Vittoria Diamanti; Vanni Lughi; Christian Klinke (Small Science, 2024)
The surface ligands in colloidal metal halide perovskites influence not only their intrinsic optoelectronic properties but also their interaction with other materials and molecules. Donor–acceptor interactions of CsPbBr3 perovskite nanocrystals with TiO2 nanoparticles and nanotubes are explored by replacing long‐chain oleylamine ligands with short‐chain butylamines. Through postsynthesis ligand exchange, the nanocrystals are functionalized with butylamine ligands while their intrinsic properties are maintained. In solution, butylamine‐capped nanocrystals exhibit reduced photoluminescence intensity with increasing TiO2 concentration but without any change in photoluminescence lifetime. Intriguingly, the Stern–Volmer plot depicts different slopes at low and high TiO2 concentrations, suggesting donor‐acceptor interaction through mixed static photoluminescence quenching and quenching sphere of action mechanism . Oleylamine‐capped nanocrystals in solution, on the other hand, show no interaction with TiO2, as indicated by consistent photoluminescence intensities and lifetimes before and after TiO2 addition. In films, both types exhibit decreased photoluminescence lifetime with TiO2, indicating enhanced donor–acceptor interaction, which is discussed in terms of electron transfer. TiO2 nanotubes enhance nonradiative recombination more in butylamine‐capped CsPbBr3 perovskite nanocrystals, emphasizing the role of ligand chain length.